Risk Factors Affecting the Incidence of Leptospirosis in Indonesia: Literature Review - Siti Hajar Husni; Martini Martini; Suhartono Suhartono (Fakultas Teknik, 2023)
Leptospirosis is a disease of animal origin or zoonoses that most commonly occurs in tropical countries. Rats are the main reservoir of Leptospira and have an important role in the incidence of leptospirosis in humans. Leptospirosis transmission is related to host factors, disease agent factors, and environmental factors. The purpose of this study was to find out the risk factors that influence the incidence of Leptospirosis. The method used in writing this article is a literature review. The source of the library used in writing this literature review is a journal article from 2017-2021 with from search process through Google Scholar and Garuda Portal. The results showed the presence of rats, the presence of livestock, the presence of standing water around the house, the condition of the living environment, and the type of work of respondents were the dominant factors that influenced the incidence of leptospirosis in Indonesia. The community is expected to maintain the cleanliness of the environment around the house and use PPE when doing risky work.